Investigation into the energy storage behaviour of layered α-V2O5 as a pseudo-capacitive electrode using operando Raman spectroscopy and a quartz crystal microbalance. Issue 36 (1st September 2017) - Yao, Minghai; Wu, Peng; Cheng, Shuang; Yang, Lufeng; Zhu, Yuanyuan; Wang, Mengkun; Luo, Haowei; Wang, Bangfen; Ye, Daiqi; Liu, Meilin
Abstract : α-V2 O5 nanowires with a layered structure have been fabricated through a two-step procedure. Abstract : α-V2 O5 nanowires with a layered structure have been fabricated through a two-step procedure. When measured as a pseudo-capacitive electrode with a three-electrode configuration in 1 M Na2 SO4 aqueous solutions, α-V2 O5 exhibits ideal capacitive characteristics with a specific capacitance of ∼238 F g −1 at a high current of 2 A g −1, but poor cycling stability with a continuous drop in the first 2000 cycles before it is maintained. To find possible solutions towards this problem, the energy storage behavior of the α-V2 O5 electrode has been carefully investigated. In situ Raman analysis suggests that it is electrolytic hydrated cations [Na(H2 O) n ] + rather than anions (SO4 2− ) that are involved in the energy storage process through reversible adsorption/desorption on the surface or intercalation/deintercalation at the interlayer of the (001) planes accompanied by interlayer spacing expansion/contraction. Moreover, the electrochemical quartz crystal microbalance results indicate that, besides a reversible mass change, there is a continuous mass loss that may originate from slow dissolution of V2 O5, which should bear the main responsibility for the poor stability (initial dramatic drop). Hence, how to inhibit dissolution, such as by coating or adding additives in the electrolyte, is found to be the key approach to improve the stability of V2 O5 based electrodes.